Packaged lives : ten stories and a novella - Zangana, Haifa, 1950- (Middle East literature in translation., 2021)
"'Packaged Lives' is a collection of ten short stories and a novella, originally written in Arabic, by Iraqi-Kurdish writer Haifa Zangana"--